2021
DOI: 10.1007/s00217-021-03819-6
|View full text |Cite
|
Sign up to set email alerts
|

Sugar and no sugar added fruit microalgae-enriched jams: a study about their physicochemical, rheological, and textural properties

Abstract: Jams are preparations of fruits whose main preserving agent is sugar. Due to this, health concerns of consumers have resulted in a sugar reduction, and its replacement using alternative sweeteners and introducing new ingredients enhancing nutritional properties. In this study, four types of fruits jams (plum, strawberry, apple, and peach), with or without sugar, were prepared using two microalgae biomass, Arthrospira platensis (Spirulina) and Chlorella vulgaris, and Dunaliella salina extract as ingredients at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…A similar effect associated with a decrease in elastic moduli compared to the control was observed with partially oxidized (4 and 8%) alginate in calcium-saturated hydrogels and agar gel with added chokeberry juice [10]. It was found that the elastic moduli of all experimental samples were many times higher compared to the elastic moduli of plum, apple, strawberry and peach fruit jams enriched with microalgae without added sugar [35].…”
Section: Structural-mechanical Properties Of Composite Jellies At Dif...supporting
confidence: 66%
“…A similar effect associated with a decrease in elastic moduli compared to the control was observed with partially oxidized (4 and 8%) alginate in calcium-saturated hydrogels and agar gel with added chokeberry juice [10]. It was found that the elastic moduli of all experimental samples were many times higher compared to the elastic moduli of plum, apple, strawberry and peach fruit jams enriched with microalgae without added sugar [35].…”
Section: Structural-mechanical Properties Of Composite Jellies At Dif...supporting
confidence: 66%
“…The oscillatory tests of tomato juices showed that the stability and the compatibility between the two different soy ingredients and tomato juice were different. Uribe‐Wandurraga et al ( 2021 ) carried out a study about the physicochemical, rheological, and textural properties of a microalgae‐enriched jam and acclaimed that Jams containing microalgae biomass‐extract showed higher G′, G″, G*, and η* values than their corresponding control samples.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, there are products with low moisture content and high water activity. For example, salted butter with 17% moisture content has a w of 0.95–0.98, whereas strawberry jelly with 34.4% moisture content has a water activity of 0.84–0.88 (da Silva et al., 2021; El‐Hajjaji et al., 2020; Schmidt & Fontana Jr., 2007; Uribe‐Wandurraga et al., 2021).…”
Section: Criteria For Low‐moisture Foods and Related Foodborne Outbreaksmentioning
confidence: 99%